Local social cohesion in indonesian rituals and its implication in educational context - Erna Mena Niman; Hieronimus Canggung Darong (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
This study critically examines the role of implicature in the Manggarai marriage proposal ritual as a culturally embedded communicative system that sustains social cohesion and collective identity in the face of accelerating global communication shifts. While dominant pragmatic theories emphasize clarity and efficiency, ritual discourse in incdigenous contexts reveals a contrasting logic where meaning is constructed through indirectness and shared cultural knowledge. Adopting a qualitative interpretive design grounded in sociopragmatics, this research integrates implicature theory and politeness theory to analyze naturally occurring discourse collected through observation, in-depth interviews, and documentation involving fifteen participants across three ritual events. Thematic analysis identifies five interrelated functions of implicature: maintaining politeness and honor, mediating negotiation, reinforcing social hierarchy, managing rejection and conflict avoidance, and enabling cultural transmission. The findings demonstrate that indirectness operates not as a strategic option but as a normative communicative system that prioritizes relational harmony over informational transparency. This challenges the universality of established pragmatic frameworks by showing that communicative effectiveness is culturally defined rather than universally fixed. Furthermore, the study advances a conceptual repositioning of implicature from a micro-level inferential process to a macro-level socio-cultural mechanism that organizes interaction and reproduces social order. Practically, the findings offer implications for developing intercultural communicative competence and culturally responsive pedagogy. By foregrounding cultural logic in meaning-making, this study contributes a novel perspective to global pragmatics, emphasizing that communication in ritual contexts is fundamentally shaped by values that sustain social cohesion and continuity